Antioxidant Activity of VCO-Clove Topical Oil and Predictive Interaction toward Prostaglandin-endoperoxide Synthase 2 - Pramitha, Dewa Ayu Ika; Wibawa, Agung Ari Chandra; Adrianta, Ketut Agus; Samidya, Ni Wayan Rias (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Pain is a prevalent symptom of various diseases, characterized by subjective sensory and emotional experiences, often triggered by nerve irritation and pain receptor activation. Prostaglandins play a crucial role as chemical mediators in pain mechanisms. Clove oil-based liniment is commonly used for pain relief, with eugenol as its main active compound. This study investigates the antioxidant activity of VCO-clove liniment with different clove proportions using the DPPH method and evaluates the analgesic potential of eugenol through its interaction with the PTGS2 receptor through in-silico analysis. VCO-clove liniment was formulated with varying clove weight ratio (1:10, 5:10, and 10:10 w/v). Antioxidant activity was evaluated in-vitro using DPPH assay, while the interaction between eugenol and PTGS2 (PDB code: 5KIR) was predicted using molecular docking. The results demonstrated that the 10:10 ratio exhibited the highest antioxidant activity, with an IC50 value of 40.33 µg/mL and an antioxidant activity index (AAI) of 0.99, classified as moderate. In-silico analysis revealed strong binding between eugenol and PTGS2, with a binding energy of -5.22 kcal/mol, suggesting its analgesic potential. In conclusion, VCO-clove liniment shows promise as an antioxidant and analgesic agent, with the 10:10 ratio displaying optimal antioxidant properties, and eugenol contributing significantly to its analgesic effects through PTGS2 interaction.